The genetical examination of 'Grasslands Ariki' ryegrass Lolium ((multiflorum x perenne) x perenne) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Plant Science - Sedcole, John Richard (Massey University, 1970)
'Grasslands Ariki' ryegrass - Lolium [(multiflorum x perenne) x perenne] - has been established in New Zealand as a successful pasture variety. While some genetic parameters were determined during its breeding programme, no diallel cross analyses have been performed on 'Ariki'. It was for this reason that this particular experiment was suggested to me. The inclusion of two treatments arose from a cynical remark passed by W. Harris, regarding the failure on the part of plant breeders to use simulated swards. The experiment was designed to determine the levels of genotype-by-environment interaction in 'Ariki' ryegrass. [FROM INTRODUCTION]
Keywords: Pastures; Grasses; Research; Seeds